The caseinolytic protease complex component CLPC1 in Arabidopsis maintains proteome and RNA homeostasis in chloroplasts - Zhang, Shoudong (BMC Plant Biol, 2018)
BACKGROUND: Homeostasis of the proteome is critical to the development of chloroplasts and also affects the expression of certain nuclear genes. CLPC1 facilitates the translocation of chloroplast pre-proteins and mediates protein degradation. RESULTS: We found that proteins involved in photosynthesis are dramatically decreased in their abundance in the clpc1 mutant, whereas many proteins involved in chloroplast transcription and translation were increased in the mutant. Expression of the full-length CLPC1 protein, but not of the N-terminus-deleted CLPC1 (ΔN), in the clpc1 mutant background restored the normal levels of most of these proteins. Interestingly, the ΔN complementation line could also restore some proteins affected by the mutation to normal levels. We also found that that the clpc1 mutation profoundly affects transcript levels of chloroplast genes. Sense transcripts of many chloroplast genes are up-regulated in the clpc1 mutant. The level of SVR7, a PPR protein, was affected by the clpc1 mutation. We showed that SVR7 might be a target of CLPC1 as CLPC1-SVR7 interaction was detected through co-immunoprecipitation. CONCLUSION: Our study indicates that in addition to its role in maintaining proteome homeostasis, CLPC1 and likely the CLP proteasome complex also play a role in transcriptome homeostasis through its functions in maintaining proteome homeostasis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12870-018-1396-0) contains supplementary material, which is available to authorized users.